Aging‐Related Decline of Glutathione Peroxidase 3 and Risk of Cardiovascular Events in Patients With Atrial Fibrillation. Issue 9 (8th September 2016) - Pastori, Daniele; Pignatelli, Pasquale; Farcomeni, Alessio; Menichelli, Danilo; Nocella, Cristina; Carnevale, Roberto; Violi, Francesco
Abstract : Background: Experimental studies demonstrated that glutathione peroxidase 3 (GPx3), an antioxidant enzyme that catabolizes hydrogen peroxide, protects against thrombosis. Little is known about its role in cardiovascular disease. Methods and Results: A prospective cohort study was conducted in 909 atrial fibrillation patients. Serum activities of GPx3, superoxide dismutase (SOD), and catalase were measured at baseline to assess the risk of cardiovascular events during a mean follow‐up of 43.4 months (3291 person‐years). Serum Nox2 and urinary excretion of 11‐deydro‐thromboxane B2 were also measured. During follow‐up 160 cardiovascular events occurred (4.9%/year). Significantly lower values of GPx3 ( P <0.001) and SOD ( P =0.037) were detected in patients with, compared to those without, cardiovascular events. A lower survival rate was observed in patients with GPx3 ( P <0.001) and SOD ( P =0.010) activities below the median, as compared to those above. In a fully adjusted Cox regression model, GPx3 was the only antioxidant enzyme predictor of cardiovascular events (hazard ratio 0.647, 95% confidence interval 0.524‐0.798, P <0.001). GPx3 was inversely associated with urinary 11‐dehydro‐thromboxane B2 (B −0.337, P <0.001) and serum Nox2 (B: −0.423, P <0.001). GPx3 activity progressively decreased with decades of age ( P <0.001), with a progressive reduction in people aged ≥70 years. Conclusions: This study provides evidence that a low antioxidant status, as depicted by reduced levels of GPx3, increases the risk of cardiovascular events in patients with atrial fibrillation. The age‐related decline of GPx3 may represent a mechanism for the enhanced cardiovascular risk in the elderly population.